Strategy and human resource management. 3rd revised ed. - Boxall, Peter; Purcell, John (Basingstoke, 2011)
"The new edition of this market leading text provides an authoratitive yet accessible account of the strategic role of HRM in organizations. Strategy and Human Resource Management 3rd edition offers fully updated chapters and sources whilst retaining the critical approach and strong framework popular with both students and lecturers."